The elevated pre‐operative plasma fibrinogen level is an independent negative prognostic factor for cancer‐specific, disease‐free and overall survival in soft‐tissue sarcoma patients. Issue 2 (7th October 2013) - Szkandera, Joanna; Pichler, Martin; Liegl‐Atzwanger, Bernadette; Absenger, Gudrun; Stotz, Michael; Ploner, Ferdinand; Stojakovic, Tatjana; Samonigg, Hellmut; Eberhard, Katharina; Leithner, Andreas; Gerger, Armin
Abstract Background and Objectives Accumulating evidence indicates an important pathophysiological role of fibrinogen on tumor cell progression and metastases in different types of cancer. The aim of the present study was to evaluate the prognostic relevance of pre‐operative fibrinogen levels on clinical outcome in a large cohort of STS patients. Methods Two hundred ninety‐four consecutive STS patients were retrospectively evaluated. Cancer‐specific survival (CSS), disease‐free survival (DFS), and overall survival (OS) were assessed using the Kaplan–Meier curves and Cox regression models. Finally, we supplemented the well‐established Kattan nomogram by the fibrinogen level and evaluated the gain of predictive accuracy of this novel nomogram by Harrell's concordance index (c‐index). Results An elevated plasma fibrinogen level was significantly associated with established prognostic factors, including age, tumor grade, size, and depth (P < 0.05). Furthermore, in multivariate analysis, increased fibrinogen levels were significantly associated with a poor outcome for CSS (HR = 2.48; 95% CI = 1.28–4.78; P = 0.007), DFS (HR = 2.00; 95% CI = 1.11–3.60; P = 0.021), and OS (HR = 2.20; 95% CI = 1.39–3.47; P < 0.001). The estimated c‐index was 0.747 using the original Kattan nomogram and 0.779 when the fibrinogen levels was added. Conclusion The pre‐operative plasma fibrinogen level may represent a strong and independent unfavorable prognostic factor for CSS, DFS and OS in STS patients. J. Surg. Oncol. 2014 109:139–144. © 2013 Wiley Periodicals, Inc.